On the dimension of the algebraic sum of subspaces - Makrides Gregoris; Szemberg Tomasz (Open Mathematics)
We provide a recursive formula for the dimension of the algebraic sum of finitely many subspaces in a finite-dimensional vector space over an arbitrary field.